EXPERIENCE OF SANITARY EPIDEMIOLOGICAL SERVICE WORK OF JEWISH AUTONOMOUS REGION IN PREVENTION OF SEVERE ACUTE RESPIRATORY SYNDROME (SARS) IMPORTATION AND DISSEMINATION - V. A. Yanovich (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Major activities of sanitary epidemiological service of Jewish Autonomous Region on organization and prevention of SARS importation and dissemination are described. Early measures include preparation of regional normativepractical documents based on analogous papers from Ministry of Public Health of Russian Federation and its introduction to the concerned services and departments. Subsequently, medical personnel training was performed to detection of SARS suspected patients and realization of primary anti-epidemic measures, informing inhabitants about preventive measures. Preparedness of hospital basis and frontier passing points was ensured.